Effective Test Infrastructure Design in the Context of Autonomous Driving - Katzorke, Nils; Kolář, Petr; Jirsák, Petr; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
Automated driving systems are of the highest public and economic interest. These systems are developed in order to increase driving safety, mobility and comfort. Furthermore, they possess the potential to increase driving efficiency and ultimately reduce transportation costs. In order to verify the functionality, testing is an inevitable step in the development process. To test the functionality of driving systems, infrastructure, such as proving grounds, targets, test benches or computer simulations, is required. Delays in the development process of test infrastructure can directly affect the development process of automated driving systems. Development time is a decisive factor for the competition between automotive manufacturers. To ensure that test infrastructure is ready to use as soon as it is required, the development process of test infrastructure should start as soon as possible. The goal of the dissertation was to develop a management concept for proactive test infrastructure development for automated driving systems. Thus, the main research question elaborated in this dissertation is “Which processes ensure the development and operation of effective test infrastructure for efficient testing of automated driving systems?” The dissertation shows that a concept for proactive test infrastructure development for automated driving systems should focus on processes that allow 1) a high number of tests that can be conducted at the test site in focus, 2) a quick adaptation of existing test infrastructure to new demands, 3) increasingly complex scenario simulations, while maintaining reproducibility, and 4) providing a broad, versatile test case portfolio. The concept considered these focus points and suggests methods for demand identification, investment prioritization, project management, implementation and operational management of new test infrastructure.
Vedoucí práce: Petr Kolář
Závěrečná práce - Institut celoživotního vzdělávání (DBA)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet